God, Nature, and Humanity in the Landscape of Lubuk Hitam Waterfall: A Seyyed Hossein Nasr Eco-Philosophy Perspective - Galang Risky Maulana; Eliza Eka Putri; Putri Rahmadani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study investigates the relationship between God, nature, and humanity through the landscape of Lubuk Hitam Waterfall in Padang, West Sumatra, using Seyyed Hossein Nasr’s eco-philosophy. Historically, the waterfall was regarded as a sacred manifestation of God in nature, fostering a deep spiritual awareness of ecological balance within the local community. Over time, however, its meaning shifted from a sacred entity to a commercial object, reflecting an anthropocentric orientation and leading to environmental degradation. This research employs a qualitative-descriptive method with a philosophical-phenomenological approach to analyze this transformation. The findings reveal that the ecological crisis surrounding the waterfall mirrors a broader spiritual crisis among the community, particularly those managing the site. Restoring the disrupted relationship between God, nature, and humanity requires spiritual education that emphasizes nature as a manifestation of the Divine. Such an approach not only fosters ecological awareness but also encourages the protection and preservation of natural sites from exploitation.